On Multiplicativity of Canonical Diagonal Forms of Matrices over the Domain of Principal Ideals. II - Prokip, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the structure of matrices over the domain of principal ideals that possess the property of multiplicativity of canonical diagonal forms.